Application of Skopos Theory in C-E Translation of Quanzhou-Specific Chinese Terms - Caiying, Wang (Advances in Social Sciences Research Journal, 2018)
This paper discusses the C-E translation of the culture-loaded items in Quanzhou,China. It includes three parts. The first part is Quanzhou’s general introduction and the classification of its culture; the second part discusses the concept of culture and theoretical issues; the last part addresses the methods to translate them readable,understandable and be faith to the original to the most extend.